Estimation of plasma levels of warfarin and 7-hydroxy warfarin by high performance liquid chromatography in patients receiving warfarin therapy - Krishna Kumar, Dhakchinamoorthi (2013)
Warfarin is one of the most commonly prescribed oral anticoagulant for prevention of thromboembolic events. The effect of this drug is measured by monitoring prothrombin time expressed as International Normalized Ratio (INR). In some cases, however, the measurement of plasma concentration of warfarin was emphasized. In the present study, reversed phase high performance liquid chromatography (HPLC) was used to estimate the plasma drug levels. A total of 185 patients were enrolled in this study. Five milliliter of venous blood was collected using sodium EDTA tubes for pharmacokinetic analysis. Solid phase extraction was used to recover the warfarin and it's metabolite from plasma using isopropanol and potassium phosphate buffer (40:60) mobile phase. Warfarin, 7-hydroxy warfarin and carbamazepine (internal standard) were separated on a C18 column and had the retention time 3.6 min, 2.9 min and 5.9 min, respectively. The assay was linear in warfarin concentration ranges of 0.1–5 μg/ml. The extraction recovery was found to be ≃85%. The mean plasma concentrations of warfarin and 7-hydroxy warfarin were found to be 3.47 ± 1.87 (SD) μg/ml, 1.25 ± 0.81 (SD) μg/ml, respectively. Through the present study the plasma concentrations of warfarin, 7-hydroxy warfarin and their metabolic ratio was determined. The assay was sensitive to follow warfarin pharmacokinetics in a patient with warfarin therapy for 3 months and above.